2001
DOI: 10.1002/cne.1133.abs
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical distribution of serotonin‐containing neurons and axons in the central nervous system of the cat

Abstract: By using a monoclonal antibody to serotonin (5-HT), an immunohistochemical study was undertaken to provide a comprehensive description of the 5-HT-containing neurons and of the distribution of their axonal processes in the cat brain and spinal cord. The localization of cell bodies was comparable to that previously reported in studies using formaldehyde-induced fluorescence and other 5-HT antibodies, with a large proportion of labeled neurons in the raphe nuclei and a minor, yet not negligible number, in the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 81 publications
5
30
0
Order By: Relevance
“…Three morphologically different serotonergic fiber types are seen in the rabbit, which correspond to the findings by others in different species: rat (Molliver, 1987;Swanson et al, 1987), cat (Mulligan and Törk, 1988;Törk et al, 1989;Léger et al, 2001), monkey Wilson and Molliver, 1991), and human (Törk, 1990). We call these fine fibers, beaded fibers, and stem-axons, according to the nomenclature established previously (Kosofsky and Molliver, 1987;Molliver, 1987;Wilson and Molliver, 1991).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Three morphologically different serotonergic fiber types are seen in the rabbit, which correspond to the findings by others in different species: rat (Molliver, 1987;Swanson et al, 1987), cat (Mulligan and Törk, 1988;Törk et al, 1989;Léger et al, 2001), monkey Wilson and Molliver, 1991), and human (Törk, 1990). We call these fine fibers, beaded fibers, and stem-axons, according to the nomenclature established previously (Kosofsky and Molliver, 1987;Molliver, 1987;Wilson and Molliver, 1991).…”
Section: Discussionsupporting
confidence: 52%
“…Studies conducted in several species have thus shown that serotonergic neurons in the dorsal raphe nucleus, the median raphe nucleus and the B9/supralemniscal area dispatch numerous serotonergic axons that primarily reach the diencephalon and telencephalon by the medial forebrain bundle in the rat (Azmitia and Segal, 1978;Moore et al, 1978;Parent et al, 1981;Steinbusch and Nieuwenhuys, 1983;Törk, 1985), cat (Jacobs et al, 1984;Léger et al, 2001), rabbit (Bjarkam et al, 1997), marmoset (Hornung and Fritschy, 1988) and man ).…”
Section: Introductionmentioning
confidence: 96%
“…Yet, studies describing the topography and the histopathology of the human raphé nuclei, where the serotonin producing and containing neurons are located, are few in number (2,(22)(23)(24). The anatomical organization of the 5-HT neurons and their projections in the brain and spinal cord, in fact, has been intensely studied only in experimental animals (25)(26)(27)(28). A first value of this study was therefore the morphologic identification in the human brainstem of all nuclei of the raphé complex, i.e., the caudal linear raphé nucleus, the dorsal raphé nucleus and the median raphé nucleus forming the rostral group, and the raphé magnus nucleus, the raphé obscurus nucleus, and the raphé pallidus nucleus forming the caudal group.…”
Section: Discussionmentioning
confidence: 99%
“…1G, 5B), which is typical of serotonergic and dopaminergic terminals (Leger et al, 2001;Mrini et al, 1995;Takeoka et al, 2009). Our manual and semiautomatic quantification method counts mostly profiles of varicosities.…”
Section: Axon and Cell Quantification Counts Of Terminal Varicositiesmentioning
confidence: 99%